An advanced BLT-humanized mouse model for extended HIV-1 cure studies. (2nd January 2018) - Lavender, Kerry J.; Pace, Craig; Sutter, Kathrin; Messer, Ronald J.; Pouncey, Dakota L.; Cummins, Nathan W.; Natesampillai, Sekar; Zheng, Jim; Goldsmith, Joshua; Widera, Marek; Van Dis, Erik S.; Phillips, Katie; et al.
Abstract : Objective: Although bone marrow, liver, thymus (BLT)-humanized mice provide a robust model for HIV-1 infection and enable evaluation of cure strategies dependent on endogenous immune responses, most mice develop graft versus host disease (GVHD), limiting their utility for extended HIV cure studies. This study aimed to: evaluate the GVHD-resistant C57 black 6 (C57BL/6) recombination activating gene 2 (Rag2) −/− γc −/− CD47 −/− triple knockout (TKO)-BLT mouse as a model to establish HIV-1 latency. Determine whether TKO-BLT mice could be maintained on antiretroviral therapy (ART) for extended periods of time. Assess the rapidity of viral rebound following therapy interruption. Design: TKO-BLT mice were HIV-1 infected, treated with various ART regimens over extended periods of time and assayed for viral rebound following therapy interruption. Methods: Daily subcutaneous injection and oral ART-mediated suppression of HIV-1 infection was tested at various doses in TKO-BLT mice. Mice were monitored for suppression of viremia and cellular HIV-1 RNA and DNA prior to and following therapy interruption. Results: Mice remained healthy for 45 weeks posthumanization and could be treated with ART for up to 18 weeks. Viremia was suppressed to less than 200 copies/ml in the majority of mice with significant reductions in cellular HIV-1 RNA and DNA. Treatment interruption resulted in rapid viral recrudescence. Conclusion: HIV-1 latency can be maintained in TKO-BLT mice over extended periods on ART and rapid viral rebound occurs following therapy removal. The additional 15–18 weeks of healthy longevity compared with other BLT models provides sufficient time to examine the decay kinetics of the latent reservoir as well as observe delays in recrudescence in HIV-1 cure studies.